The Effect of Some Climatic Parameters on Temporal Variations of Sand and Dust Storm Events Over Riyadh, Saudi Arabia - Al-Hajji, Zakiah; Munir, Said; Al- Qahtani, Jumaan; Alexiou, Ioannis; Hafez, Mohamed (Geography, Earth Science and Environment: Research Highlights Vol. 10, 2025)
This study examines the decreasing incidence of sand and dust storm (SDS) events in Riyadh, Saudi Arabia, emphasizing their environmental and social impacts. Dust and sand storms (SDS) are prevalent in arid regions like the Arabian Peninsula, significantly impacting environmental conditions and human health. SDS events are natural phenomena that adversely affect air quality and human health, as well as the local economy. The objective of the study is to analyze the relationship between climatic factors such as temperature, precipitation, wind speed, and atmospheric pressure, and the occurrence of dust from 2007 to 2023, identifying spatial and temporal patterns. A multiple linear regression model was employed to assess data from the National Center for Meteorology, revealing a significant positive correlation between rising temperatures and SDS events, where a one-unit increase in temperature leads to an increase of 0.186 in the frequency of dust occurrences. Conversely, increased atmospheric pressure and precipitation are associated with decreases in dust occurrences. Additionally, lower wind speeds significantly reduce the number of events. Based on the study's findings, it is recommended that temperature be used as an indicator or predictor for SDS events in forecasting models, enhancing the ability to predict these phenomena and promoting sustainable environmental management strategies.